Quasi-topological fractons: a 3D dipolar gauge theory - Erica Bertolini; Alberto Blasi; Nicola Maggiore (European Physical Journal C: Particles and Fields)
Abstract We consider the theory of a generic rank-2 tensor field in three spacetime dimensions, which involves a symmetric tensor field transforming under infinitesimal diffeomorphisms, and a vector field, whose gauge transformation depends on a local vector parameter. The gauge fixing shows a non-trivial structure, and some non-intuitive possibilities are listed. Despite the fact that the theory is not topological, the energy-momentum tensor vanishes on-shell, which justifies the “quasi-topological” appellation we give to this theory. We show that the theory has three degrees of freedom. Moreover, we find an interesting physical interpretation, which consists in a generalized planar electromagnetism and in the emergence of two vector charges with restricted mobility. These are typical fractonic behaviours which can be related to the so-called traceless scalar and vector charge theories.